PERANCANGAN SITUS WEB DRAMA THAILAND TERBARU MENGGUNAKAN FRAMEWORK LARAVEL - Agnes Asriliyanti; Angga Septian M.N. (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Thai drama is entertainment that is currently popular among Indonesian teenagers. even spread all over the world. There are many ways to access Thai dramas, one of which is by downloading or streaming them on certain websites. The author understands that there are still many Thaientu (a term for Thai drama lovers) who are often confused about finding and preparing a website that provides the latest streaming links to watch Thai drama shows on local Thai TV. Therefore, the authors develop a website that provides link updates from five other websites as streaming link providers. Website development uses the PHP programming language and the Laravel Framework which makes the website more attractive and provides links from five websites (youtube.com, Viu.com, Wetv.com, Imdb.com and Mydramalist.com). . In addition, the retrieved information is entered into a local database, making it useful for faster drama searches. The result of implementing the Laravel Framework is that the developed website is capable of displaying Thai drama links based on predetermined categories. The categories are Popular Thai dramas, and Completed Thai dramas and Mixed dramas. The links displayed come from five other websites that have been predetermined. Thus, one will save their time and do not need to open every website to find the desired link using this website.